(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Ulcers result from imbalanced factors that attack the stomach lining (pepsin, acid, NSAIDs) and those that protect it, and free radical-associated damage. This research aims to understand how the roots of Abroma augusta can mitigate ethanol-induced gastric ulcers in rats. Omeprazole (20 mg/kg) and root extract (250 mg/kg/p.o and 500 mg/kg/p.o) were administered for 21 days. Before ethanol administration (1 ml/200 g), the animals were fasted for 24 hours. Parameters like Ulcer Index, % inhibition of ulceration, plasma anti-oxidant levels and Histopathology were assessed. The present study revealed that the 500 mg/kg root extract possesses significant effect, which may be the presence of tannins, saponins, and alkaloids. The extract effectively countered ethanol-induced lesion formation and maintained plasma superoxide dismutase (p <0.01), catalase (p <0.05), and lipid peroxidase (p <0.01) levels. At a dosage of 500 mg/kg, the root extract exhibited notable effectiveness in safeguarding the histological integrity of the gastric mucosa. This study has provided documentary evidence for the antiulcer property of Abroma augusta for its activity.